Disney Princess Storybook Collection - Disney (UK Parragon Books Ltd, 2015)
Join the Disney Princesses on their royal adventures! This beautiful collection includes five stories: Belle and the Perfect Pearl Cinderella and the Lost Mice Ariel and the Aquamarine Jewel Rapunzel and the Crown Jewels Merida's Wild Ride